1992
DOI: 10.1007/bf00034308
|View full text |Cite
|
Sign up to set email alerts
|

Survival and growth of pea protoplasts after transformation by electroporation

Abstract: Protoplasts from two different pea cultivars, Belman and Filby, were stably transformed by direct gene transfer using electroporation. Transgenic calli could be obtained after selection, when hygromycin resistance was used as the selective trait introduced into the protoplasts, while no transformants were obtained when kanamycin resistance was used as selective marker in either of the two pea cultivars tested. The effect of the field strength on survival and division rates of the protoplasts was studied. Two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Transient gene expression following protoplast electroporation was reported only seldom in pea (Hashimoto et al 1992;Puonti-Kaerlas et al 1992;Ochatt et al 2005), and the determination of the optimum electrical parameters permitting entry of the foreign information into protoplasts whilst permitting their subsequent viability and proliferation competence was a prerequisite for success in this domain. Conversely, there are quite a few examples of electroporation applied for transient and (less frequently) stable gene transfer in other legume species, as will be discussed crop-wise below.…”
Section: Electroporationmentioning
confidence: 97%
See 3 more Smart Citations
“…Transient gene expression following protoplast electroporation was reported only seldom in pea (Hashimoto et al 1992;Puonti-Kaerlas et al 1992;Ochatt et al 2005), and the determination of the optimum electrical parameters permitting entry of the foreign information into protoplasts whilst permitting their subsequent viability and proliferation competence was a prerequisite for success in this domain. Conversely, there are quite a few examples of electroporation applied for transient and (less frequently) stable gene transfer in other legume species, as will be discussed crop-wise below.…”
Section: Electroporationmentioning
confidence: 97%
“…Several conclusions were obtained in experiments focused on the utilisation of various genes for resistance to antibiotics as selective genes, particularly kanamycin. Puonti-Kaerlas (1992), De Kathen and Jacobsen (1990) as well as Schroeder et al (1993) found kanamycin less effective for selection than hygromycin and phosphinotricin. On the other hand, Grant et al (1998) deemed kanamycin in higher concentrations and in combination with successive selection steps as effective.…”
Section: Agrobacterium-mediated Transformationmentioning
confidence: 97%
See 2 more Smart Citations
“…Protoplasts from two pea cultivars were stably transformed by direct DNA transfer using electroporation (Puonti-Kaerlas et al, 1992a). Transgenic calli were obtained after selection with hygromycin, whereas no transformants were obtained when kanamycin was used for selection.…”
Section: Direct Dna Transfermentioning
confidence: 99%